Synergy in the urban solid waste management system in Malolos City, Philippines - Tinio, Marion Micah R.; Moya, Tolentino B.; Rollon, Analiza P. (2019)
The paper demonstrates through system dynamics modelling how the following variables work together in the urban solid waste management (USWM) system: population, city income, public participation, composting and recycling, and greenhouse gas emissions. Malolos City, Philippines, is used as a case study for three ten-year model scenarios: (1) USWM with no composting and recycling, (2) USWM with an operational materials recovery and composting facility (MRCF), and (3) USWM with operational MRCF and incorporated effects of public participation towards solid waste management practices. The operation of the MRCF in Scenario 2 reduced total volume of disposed solid waste by about 25,000 tons but increased total expenses for solid waste management by about PhP 37M. The incorporation of the effects of public participation in Scenario 3 further reduced the volume of disposed solid waste by about 103,900 tons; reduced the volume of generated solid waste by around 101,000 tons; and allowed the informal collection of 9,966 tons of recyclables. Estimates of CH4 and CO2 emissions also decreased in Scenario 3. The results revealed how composting and recycling and public participation affects the USWM through reduced waste volumes and increased savings. (Author's abstract)